The Relationship Between Premenstrual Symptoms and Healthy Lifestyle Behaviours in the COVID-19 Pandemic - Hacer Ataman and Merve Tuncer (Professor Despina Sapountzi-Krepia, 2024)
The Relationship Between Premenstrual Symptoms and Healthy Lifestyle Behaviours in the COVID-19 Pandemic